Hubungan Antara Komunikasi Interpersonal Mentor Dan Anak PPA Dengan Keterampilan Sosial Remaja - Suki, Melfri; Andung, Petrus Ana; Meilawati, Fitria Titi (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
The adolescent phase is a phase in the achievement of a very prominent self-identity, increasingly logical, abstract and ideal thinking Introducing adolescents to the outside world is very important for children's cognitive development. With PPA can shape children's social skills through interpersonal communication, teaching and programs that will be applied from the time the child enters the beginning to PPA until the child finishes and is considered capable of becoming a mature Christian person in faith, thought and also able to become a leader over himself and others. In this case, the design is made for teaching and programs that cover the themes, topics and concepts studied, including materials, experiences and processes by which mentors interact in order to achieve predetermined goals, namely holistic child development goals which include socio-emotional, intellectual, spiritual and physical (children's physical health). This study aims to analyze how much the Interpersonal Communication Relationship between Mentors and PPA Children Aged 15-18 Years with Adolescent Social Skills at PPA Bethlehem IO-722 West Oesapa. The theory used in this study is the Source Credibility Theory. Based on the results of the Pearson Correlation analysis between the variables of Interpersonal Communication (X) and Adolescent Social Skills (Y), it is known that the significance value is 0.000< 0.05. Thus, the hypothesis that reads there is a positive relationship between interpersonal communication mentors and PPA children aged 15-18 years with adolescent social skills. Data analysis using the Pearson Correlation Test (Product Moment) obtained r calculate 0.657. So based on rtable with a confidence level of 0.05 (rtable for 55 subjects with a confidence level of 5% is 0.265), it is understood that r count > r table (0.657>0.265) then Ha is accepted thus there is a significant relationship between interpersonal communication and social skills. Based on that, it can be concluded that the level of strength of the relationship is in the strong category. Also, positive values indicate a unidirectional relationship between Interpersonal Communication and Social Skills.